Roadmap on 3D integral imaging: sensing, processing, and display - Javidi, Bahram; Carnicer, Artur; Arai, Jun; Fujii, Toshiaki; Hua, Hong; Liao, Hongen; Martínez-Corral, Manuel; Pla, Filiberto; Stern, Adrian; Waller, Laura; Wang, Qiong-Hua; Wetzstein, Gordon; et al. (Optics express, 2020)
This Roadmap article on three-dimensional integral imaging provides an overview of some of the research activities in the field of integral imaging. The article discusses various aspects of the field including sensing of 3D scenes, processing of captured information, and 3D display and visualization of information. The paper consists of a series of 15 sections from the experts presenting various aspects of the field on sensing, processing, displays, augmented reality, microscopy, object recognition, and other applications. Each section represents the vision of its author to describe the progress, potential, vision, and challenging issues in this field.